1036 Operative Versus Non-Operative Management of Osteoporotic Femoral Fractures. (12th October 2021) - Lenihan, J; Waseem, S; Rawal, J; Hull, P; Carrothers, A; Chou, D
Abstract: Background: he incidence of diaphyseal and distal osteoporotic femoral fractures (OFFs) is increasing. This cohort of patients is often frail with multiple medical co-morbidities. No published data exists neither reporting severity of pain associated with these fractures nor pain in managing their fractures. There are no comparative studies investigating outcomes between conservative (CM) and surgical management (SM). We investigated pain and outcomes between CM and SM OFFs. Method: We retrospectively analysed all OFFs admitted to our unit between 2018-2019. We analysed electronic patient records including patient-reported pain scores (PRPS). PRPS were calculated for set time periods: admission; 0-24hours CM versus day 1 post-operative; day 2-3; day 4-5. Primary outcome measure was PRPS. Secondary outcome measures included use of traction; PCA use; weightbearing status; length of stay (LOS); 30 day and 1 year mortality. Data was statistically analysed using SPSS software. Results: 22 patients were recruited (11CM, 11SM). There was no statistical difference between groups in terms of age; sex; cognition; Charlson Index; nor pre-morbid mobility status. There was no statistical difference for pain at admission nor PCA use. SM were less painful in the first 24-hour period postoperatively and in the first 3-day postoperative period compared to the same time period in CM. There was no difference in PRPS for the 72–120-hour period. There was no statistical difference between LOS; NWB status; 30 day nor 1 year mortality. Conclusions: Operating on OFFs reduces pain in the perioperative period without increasing mortality or LOS in this frail population.